Deletion of Proton Gradient Regulation 5 (PGR5) and PGR5-Like 1 (PGRL1) proteins promote sustainable light-driven hydrogen production in Chlamydomonas reinhardtii due to increased PSII activity under sulfur deprivation - Steinbeck, Janina; Nikolova, Denitsa; Weingarten, Robert; Johnson, Xenie; Richaud, Pierre; Peltier, Gilles; Hermann, Marita; Magneschi, Leonardo; Hippler, Michael (Frontiers in Plant Science, 2015)
Continuous hydrogen photo-production under sulfur deprivation was studied in the Chlamydomonas reinhardtii pgr5 pgrl1 double mutant and respective single mutants. Under medium light conditions, the pgr5 exhibited the highest performance and produced about 8 times more hydrogen than the wild type, making pgr5 one of the most efficient hydrogen producer reported so far. The pgr5 pgrl1 double mutant showed an increased hydrogen burst at the beginning of sulfur deprivation under high light conditions, but in this case the overall amount of hydrogen produced by pgr5 pgrl1 as well as pgr5 was diminished due to photo-inhibition and increased degradation of PSI. In contrast, the pgrl1 was effective in hydrogen production in both high and low light. Blocking photosynthetic electron transfer by DCMU stopped hydrogen production almost completely in the mutant strains, indicating that the main pathway of electrons towards enhanced hydrogen production is via linear electron transport. Indeed, PSII remained more active and stable in the pgr mutant strains as compared to the wild type. Since transition to anaerobiosis was faster and could be maintained due to an increased oxygen consumption capacity, this likely preserves PSII from photo-oxidative damage in the pgr mutants. Hence, we conclude that increased hydrogen production under sulfur deprivation in the pgr5 and pgrl1 mutants is caused by an increased stability of PSII permitting sustainable light-driven hydrogen production in Chlamydomonas reinhardtii.